A Review on the Critical Success Factors (CSFs) in the Operation of Hotels - Nazari, Narges (ASEAN Journal on Hospitality and Tourism, 2018)
Abstract: Critical Success Factors (CSFs) have been recognized as an important and powerful approach for the competitiveness and success of the hospitality organizations in particular hotels in the tourism industry. The implementation of some core capabilities, activities, and facilities may provide better opportunities for the hoteliers to be successful in the intensive marketplace. This article studies the CSFs for the hotels? operation in the past studies. To do this, the hotel-related CSFs for operation of different types of hotels were first compiled through the review literature. Then, the main issues, gaps, and conditions of the studies have been considered. Further studies are also suggested based on the identified gaps in the reviewed literature.